2020
DOI: 10.1590/1678-7757-2020-0191
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and morphological changes produced by ionizing radiation on bone tissue surrounding dental implant

Abstract: Biomechanical and morphological changes produced by ionizing radiation on bone tissue surrounding dental implant Objective: This study analyzed the effect of ionizing radiation on bone microarchitecture and biomechanical properties in the bone tissue surrounding a dental implant. Methodology: Twenty rabbits received three dental morse taper junction implants: one in the left tibia and two in the right tibia. The animals were randomized into two groups: the nonirradiated group (control group) and the irradiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The effect of ionizing radiation on peri-implant bone was confirmed by animal studies and it seems that radiation therapy negatively influences the microarchitecture and biomechanical properties of bone tissue, especially near the surface of the implant. 22,23 Earlier research concluded, though, that the survival of nasal implants is not influenced by radiotherapy. 5,12 Our study confirms this observation as an equal proportion of nasal implants were lost by irradiated and nonirradiated patients.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of ionizing radiation on peri-implant bone was confirmed by animal studies and it seems that radiation therapy negatively influences the microarchitecture and biomechanical properties of bone tissue, especially near the surface of the implant. 22,23 Earlier research concluded, though, that the survival of nasal implants is not influenced by radiotherapy. 5,12 Our study confirms this observation as an equal proportion of nasal implants were lost by irradiated and nonirradiated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation affecting the vasculature of bone induces changes in the Haversian canal and sclerosis of the connective tissue in the marrow, a phenomenon which was first reported by Ewing in 1926(Ewing 1926. Investigations with long bone, and some also in jawbone, have shown that irradiation has many detrimental effects on the vasculature supplying osteogenic cells (1) reducing the blood flow by damaging vascular endothelial cells, (2) evoking a constriction and obliteration of blood vessels in the bone-forming area, and (3) diminishing the perfusion of osteogenic cells (Curi et al 2007;Poort et al 2017Soares et al 2020). In vitro studies revealed a reduced expression of vascular endothelial growth factor (VEGF), essential for blood vessel development, with doses less than 8 Gy.…”
Section: Irradiation and Changes In The Bone's Vasculaturementioning
confidence: 92%
“…Additionally, non-healing bone necrosis during the ORN development process can trigger a series of unfavorable incidents that cause decreased implant stability and even implant loss (37). In an in vivo study, Soares et al investigated the biomechanical and morphological changes caused by ionizing radiation in the bone tissue surrounding 20 rabbit dental implants (38). The choice of rabbits was made to provide an excellent short-term analysis of the osseointegration process because of their similar Haversian systems to human beings and a three-fold faster rate of bone turnover.…”
Section: The Impact Of Radiotherapy On Osseointegration and Survival ...mentioning
confidence: 99%
“…Because they are more radiosensitive than other bone cells, osteoblasts are the first to experience apoptotic cell death after direct tissue damage or hypoxic/malnourished conditions caused by ionizing radiation (52). Furthermore, it is suggested RT changes collagen modulation, which in turn slows the mineralization process and contributes to implant failure (38). Ionizing radiation may also have an effect on osteoblast activity by impeding normal deposition and the production of crystals of hydroxyapatite from the inorganic matrix (53,54).…”
Section: The Impact Of Radiotherapy On Osseointegration and Survival ...mentioning
confidence: 99%